2015
DOI: 10.1007/s12022-015-9395-2
|View full text |Cite
|
Sign up to set email alerts
|

Monomorphous Plurihormonal Pituitary Adenoma of Pit-1 Lineage in a Giant Adolescent with Central Hyperthyroidism

Abstract: Thyrotropin (TSH)-secreting pituitary adenomas are exceedingly rare at the pediatric age and no cases of co-secretion with other pituitary hormones in these tumors have been described in this age range. We present a case of a monomorphous plurihormonal pituitary adenoma that co-secreted TSH and GH in a pediatric patient. A 13-year-old male presented with increasing height velocity (17.75 cm/year, 9.55SD), weight loss, and visual impairment. Initial biochemical evaluations revealed secondary hyperthyroidism. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
20
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 47 publications
3
20
0
2
Order By: Relevance
“…Similar to a recent case that we reported but did not include in this cohort, 23 our results also highlight that silent subtype 3 adenomas should be added to the list of Pit-1 lineage adenomas that can present with scattered fibrous bodies, similar to acidophil stem cell adenomas, [3][4][5] which also express Pit-1. However, acidophil stem cell adenomas are distinguished from silent subtype 3 adenomas by their oncocytic nature and predominant diffuse cytoplasmic staining pattern for PRL with only focal GH expression to indicate plurihormonality in some cases.…”
Section: Discussionsupporting
confidence: 89%
“…Similar to a recent case that we reported but did not include in this cohort, 23 our results also highlight that silent subtype 3 adenomas should be added to the list of Pit-1 lineage adenomas that can present with scattered fibrous bodies, similar to acidophil stem cell adenomas, [3][4][5] which also express Pit-1. However, acidophil stem cell adenomas are distinguished from silent subtype 3 adenomas by their oncocytic nature and predominant diffuse cytoplasmic staining pattern for PRL with only focal GH expression to indicate plurihormonality in some cases.…”
Section: Discussionsupporting
confidence: 89%
“…This clustering of CNFPA was previously reported by our group 19 and correlates with the clinical behavior of these tumors 20 . Similarly, the clustering of POU1F1-dependent tumors is congruent with the finding of plurihormonal tumors capable of synthesizing GH, PRL and TSH in different combination 21 . Thus, it appears that these three transcription factors drive not only normal gland cytodifferentiation but also pituitary tumorigenesis.…”
Section: Discussionsupporting
confidence: 76%
“…Simultaneously, some patients showed acromegaly with hyperprolactinemia (11) or hyperthyroidism (16,17). Plurihormonal TSHomas with hypersecretion of GH revealed acromegaly usually masks secondary hyperthyroidism (17,18). A unique study revealed a plurihormonal TSHoma hypersecretion of TSH, GH, and FSH (14).…”
Section: Discussionmentioning
confidence: 99%